Canine Antibodies against Salivary Recombinant Proteins of Phlebotomus perniciosus: A Longitudinal Study in an Endemic Focus of Canine Leishmaniasis. - Tatiana Kostalova; Tereza Lestinova; Petra Sumova; Michaela Vlkova; Iva Rohousova; Eduardo Berriatua; Gaetano Oliva; Eleonora Fiorentino; Aldo Scalone; Marina Gramiccia; Luigi Gradoni; Petr Volf (Public Library of Science (PLoS), 2015)
BACKGROUND:Phlebotomine sand flies are vectors of Leishmania parasites. During blood feeding, sand flies deposit into the host skin immunogenic salivary proteins which elicit specific antibody responses. These anti-saliva antibodies enable an estimate of the host exposure to sand flies and, in leishmaniasis endemic areas, also the risk for Leishmania infections. However, the use of whole salivary gland homogenates as antigen has several limitations, and therefore, recombinant salivary proteins have been tested to replace them in antibody detection assays. In this study, we have used for the first time sand fly salivary recombinant proteins in a longitudinal field study on dogs. METHODOLOGY/PRINCIPAL FINDINGS:Sera from dogs naturally exposed to P. perniciosus bites over two consecutive transmission seasons in a site endemic for canine leishmaniasis (CanL) were tested at different time points by ELISA for the antibodies recognizing whole saliva, single salivary 43 kDa yellow-related recombinant protein (rSP03B), and a combination of two salivary recombinant proteins, 43 kDa yellow-related protein and 35.5 kDa apyrase (rSP01). Dogs were also tested for Leishmania infantum positivity by serology, culture, and PCR and the infection status was evaluated prospectively. We found a significant association between active CanL infection and the amount of anti-P. perniciosus saliva antibodies. Importantly, we detected a high correlation between IgG antibodies recognizing rSP03B protein and the whole salivary antigen. The kinetics of antibody response showed for both a whole saliva and rSP03B a similar pattern that was clearly related to the seasonal abundance of P. perniciosus. CONCLUSIONS:These results suggest that P. perniciosus rSP03B protein is a valid alternative to whole saliva and could be used in large-scale serological studies. This novel method could be a practical and economically-sound tool to detect the host exposure to sand fly bites in CanL endemic areas.